2021
DOI: 10.1186/s43161-021-00023-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole-body vibration on quadriceps and hamstring muscle strength, endurance, and power in children with hemiparetic cerebral palsy: a randomized controlled study

Abstract: Background Hemiplegic cerebral palsy (CP) enormously affects the quadriceps and hamstring muscles. It causes weakness in the affected lower-extremity muscles in addition to muscle imbalance and inadequate power production, especially in the ankle plantar-flexor and knee extensor muscles. It also causes anomalous delayed myoelectrical action of the medial hamstring. A whole-body vibration (WBV) exercise can diminish muscle spasticity and improve walking speed, muscle strength, and gross motor fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Overall, changes in muscular strength in all three groups tended to improve. This is consistent with previous studies that blood flow restriction training was found to improve muscular strength (Cai et al, 2021;Cohen et al, 2022) or even whole-body vibration training alone can also increase muscular strength (Berner et al, 2020;Hegazy et al, 2021;Lai et al, 2021). This was especially true in the WBV+HYP group, where changes were similar to those in the BFR group.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, changes in muscular strength in all three groups tended to improve. This is consistent with previous studies that blood flow restriction training was found to improve muscular strength (Cai et al, 2021;Cohen et al, 2022) or even whole-body vibration training alone can also increase muscular strength (Berner et al, 2020;Hegazy et al, 2021;Lai et al, 2021). This was especially true in the WBV+HYP group, where changes were similar to those in the BFR group.…”
Section: Discussionsupporting
confidence: 92%
“…For different reasons, 43 full-text papers were read in depth for eligibility, and 30 articles were removed. Finally, this meta-analysis comprised 13 papers [10,11,[23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Resultsmentioning
confidence: 99%
“… 12 - Ritzman et al 13 Ahberg (2006) 31 25-40 4 6 25.7 Cheng (2015) 32 20 2 5 3.2 Eklund (1969) 33 100-200 1.5 1-2 241.2 (?) Li et al 18 El-Bagalaty (2021) 34 5-25 0-3.9 20 9.8 Duran (2020) 35 8-20 1-2 15 3.2 Gusso (2016) 36 15-20 1 9 1.6 Cai et al 25 Yin (2019) 37 12 4 6-15 2.3 TeKin (2021) 38 15 4 15 3.6 Hegazy (2021) 39 10-25 2 10 5.0 …”
Section: Survey Of Current Clinical Studies Of Wbvt For Children With...mentioning
confidence: 99%